Extent to Which Microteaching Enhances Classroom Management Competencies among Physics Teacher Trainees in Selected Public Universities in Western Kenya - Kulu Dorcas Mutheu; Jafred Muyaka; Peter Waswa (Journal of Advances in Education and Philosophy, 2026)
Classroom management competence is a fundamental professional skill that determines teachers' ability to create and sustain effective learning environments. Despite its importance, many novice teachers experience difficulties in maintaining learner discipline, managing classroom routines, and sustaining learner engagement during instruction. Microteaching has increasingly been recognized as an important teacher preparation strategy that provides pre-service teachers with opportunities to develop classroom management competencies through repeated practice, constructive feedback, and reflective learning. This study determined the extent to which microteaching enhances classroom management competencies among physics teacher trainees in selected public universities in Western Kenya. Guided by Vygotsky's Social Development Theory, the study adopted a convergent parallel mixed-methods research design. The target population comprised physics teacher trainees, physics teacher educators, and Heads of Physics Departments from four public universities. Data were collected using questionnaires, observation schedules, interview schedules, and document analysis guides. Quantitative data were analyzed using descriptive and inferential statistics, while qualitative data were analyzed thematically. The findings revealed that microteaching significantly enhanced trainees' classroom management competencies, particularly in maintaining learner discipline, managing lesson transitions, engaging learners actively, improving classroom movement and positioning, and teaching through demonstration. Inferential analysis further established that microteaching had a statistically significant positive influence on classroom management competence (t = 12.907, p < .001). However, classroom observations indicated that some trainees had not fully translated perceived competence into consistent classroom practice. The study concludes that microteaching is an effective instructional approach for developing classroom management competencies among physics teacher trainees. The study recommends strengthening reflective supervision, increasing opportunities for repeated microteaching sessions, and integrating authentic classroom experiences into teacher education programmes to enhance classroom management competence before teaching practice.